2020
DOI: 10.1016/j.nedt.2020.104442
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of nursing students participating in end-of-life education programs: A systematic review and qualitative metasynthesis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
3
9
0
1
Order By: Relevance
“…This study examined two revisions of the original 30-item FATCOD in which the scale was reduced to a subset of functioning items [16,17]. Seven items (8,9,11,13,14,26,28) were selected in both studies. Five items (3,5,6,7,15) were only retained in the previous study of the authors [16] and 2 items (25,29) were isolated in the study of Browall and colleagues [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study examined two revisions of the original 30-item FATCOD in which the scale was reduced to a subset of functioning items [16,17]. Seven items (8,9,11,13,14,26,28) were selected in both studies. Five items (3,5,6,7,15) were only retained in the previous study of the authors [16] and 2 items (25,29) were isolated in the study of Browall and colleagues [17].…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, there has been an increase in palliative care curricula in medical and nursing schools in recent decades worldwide. Medical educators have defined guidelines on essential contents for adequate training in palliative care and proposed teaching methods to train medical and nursing students on interpersonal and communication skills in end-of-life care, often from a teaching perspective [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the content of palliative care education, the students specified which teaching methods they preferred. Earlier literature has confirmed that various methods are effective at enhancing students’ palliative care learning [ 22 , 23 , 48 ], with this study providing a unique, detailed view of which aspects of palliative care and which teaching methods they prefer.…”
Section: Discussionmentioning
confidence: 69%
“…Ruiz-Pellón's et al. [ 12 ] review concluded that simulation activities conveyed a feeling of safety and ease. These results were in line with our participants’ experience.…”
Section: Discussionmentioning
confidence: 99%
“…As an experiential learning method, the simulation was increasingly accepted as a preparation, substitute, or supplement for hospice clinical practice. One systematic review, which included the end-of-life education programs from 2008 to 2018, concluded that simulation-based activities were the primary educational method and were considered valuable and beneficial for learning in end-of-life education programs [ 12 ].…”
Section: Introductionmentioning
confidence: 99%